Sustainable 3D printing of bone scaffolds using animal biowaste feedstocks - A. Dukle; M. Ravi Sankar (Next Sustainability)
Numerous 3D printing feedstocks are currently being studied for the 3D printing of bone scaffolds for bone regeneration, with differing degrees of success. Most of these feedstocks are produced using ceramics, polymers, and composites. However, the currently available feedstocks are costly and have a significant impact on the environment during production and distribution. On the other hand, every day, a large amount of biowaste is produced from plant, animal, and microbial sources, which are becoming increasingly difficult to manage. Therefore, there is always a demand for efficient disposal and recycling methods. This study provides an overview of the use of biowaste-derived 3D printing feedstocks for bone tissue engineering applications. In recent years, biowaste, which is a renewable and cost-effective source, has been explored as a potential alternative to conventional feedstocks. This paper covers various types of animal derived biowastes and highlights their potential advantages for bone tissue engineering. It also discusses different properties, including rheology, mechanical strength, printability, and bioactivity for bone tissue engineering applications. The study also addresses the challenges and future perspectives of biowaste-derived feedstocks for bone tissue engineering, including regulatory hurdles, biocompatibility, and scalability.